2022
DOI: 10.3389/fnut.2022.796362
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Day Intervention With Granola Containing Cereal Beta-Glucan Improves Glycemic Response and Changes the Gut Microbiota in Healthy Individuals: A Crossover Study

Abstract: Intake of soluble fibers including beta-glucan, is known to improve post-prandial glycemic response. The mechanisms have been attributed to the viscous gel forming in the stomach and small intestine, giving a longer absorption time. However, recent evidence suggests a link between intake of beta-glucan and improved glycemic regulation at subsequent meals through the gut microbiota. We investigated the short-term effect of granola with different amounts of cereal beta-glucan on glycemic response and gut microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 80 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…The HTCS consists of a single protein that extends across the cytoplasmic membrane and includes domains found in a typical two-component system: an extracellular sensor at the N-terminus, a cytoplasmic histidine kinase, and a response regulator [ 101 ]. The HTCS detects signals through the direct attachment of oligosaccharide fragments to the periplasmic sensor domain [ 102 ]. These oligosaccharides, results of polysaccharide breakdown by endo-acting enzymes encoded within the PUL anchored to the cell surface, are first moved into the periplasm by the SusC homolog, a TonB-dependent transporter.…”
Section: Human Gut Bacteria’s Affinity For β-Glucanmentioning
confidence: 99%
“…The HTCS consists of a single protein that extends across the cytoplasmic membrane and includes domains found in a typical two-component system: an extracellular sensor at the N-terminus, a cytoplasmic histidine kinase, and a response regulator [ 101 ]. The HTCS detects signals through the direct attachment of oligosaccharide fragments to the periplasmic sensor domain [ 102 ]. These oligosaccharides, results of polysaccharide breakdown by endo-acting enzymes encoded within the PUL anchored to the cell surface, are first moved into the periplasm by the SusC homolog, a TonB-dependent transporter.…”
Section: Human Gut Bacteria’s Affinity For β-Glucanmentioning
confidence: 99%
“…When different amounts of cereal β-glucan (low: 0.8 g, medium: 3.2 g, and high: 6.6 g) were consumed in the evening meal for three days, only the medium intervention was able to reduce blood glucose and insulin during glucose tolerance (OGT) testing in the following day when compared to baseline. The authors considered the beneficial effects of β-glucan on glycemic regulation the following day are not dependent on viscosity [ 77 ]. However, some studies confirmed the dose–response hypothesis of β-glucan in relation to the glycemic response postprandial [ 67 , 73 ].…”
Section: Human Studies With Dietary Fibers and Glycemic Responsementioning
confidence: 99%
“…19 In particular, proven health benefits are glucose and cholesterol lowering effect, which reduce the risk of type II diabetes and cardiovascular disease [20][21][22] by reducing serum low-density lipoprotein (LDL)-cholesterol, improving glycaemic response and modulation of gut microbiota. 23,24 Cholesterol and plasma glucose lowering effect of βG is also associated with the increase in the viscosity of chyme, which affects gastrointestinal motility and hydrolysis rate in the GIT. 25 In addition to the higher viscosity effect in the upper GIT, βG may also alter the microviscosity of the mucus layer in the small intestine, hence decreasing its permeability by increasing overall polymer concentrations and decreasing porocity.…”
Section: Introductionmentioning
confidence: 99%
“…19 In particular, proven health benefits are glucose and cholesterol lowering effect, which reduce the risk of type II diabetes and cardiovascular disease 20–22 by reducing serum low-density lipoprotein (LDL)-cholesterol, improving glycaemic response and modulation of gut microbiota. 23,24 Cholesterol and plasma glucose lowering effect of βG is also associated with the increase in the viscosity of chyme, which affects gastrointestinal motility and hydrolysis rate in the GIT. 25…”
Section: Introductionmentioning
confidence: 99%